2022
DOI: 10.1007/s13202-022-01596-w
|View full text |Cite
|
Sign up to set email alerts
|

Review of underbalanced drilling techniques highlighting the advancement of foamed drilling fluids

Abstract: Overbalanced drilling is the most common drilling technique; nevertheless, it has several disadvantages such as formation damage, mud losses, and stuck pipes; challenges that are common in high permeability zones and highly fractured formations. To overcome those issues, the underbalanced drilling method could be implemented. The underbalanced drilling (UBD) technique is widely utilized in hard, under pressure, depleted, and fractured/vuggy formations. Low-density drilling fluids are usually used in UBD operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…34 In other words, the n L value can reflect the resistance of liquid migration between bubbles laterally. Equation (4) shows that the value of n L is related to the foam quality Γ and bubble radius r B , and considering the difference in the growth of Γ and r B , the value of n L increases simultaneously with Γ in this experiment. Therefore, the transport resistance of liquid between bubbles is continuously reduced with the increase in bubble quality.…”
Section: Foam Qualitymentioning
confidence: 72%
See 1 more Smart Citation
“…34 In other words, the n L value can reflect the resistance of liquid migration between bubbles laterally. Equation (4) shows that the value of n L is related to the foam quality Γ and bubble radius r B , and considering the difference in the growth of Γ and r B , the value of n L increases simultaneously with Γ in this experiment. Therefore, the transport resistance of liquid between bubbles is continuously reduced with the increase in bubble quality.…”
Section: Foam Qualitymentioning
confidence: 72%
“…Foam is a reservoir mobility control system that has been widely proven to be effective 1,2 . Since the 1960s, extensive theoretical research and field practice have proved the significance of foam in oilfield work, and the current application of foam has included drilling, fracture acidizing, and enhanced oil recovery (EOR), 3–6 among others. The special flow state of the foam makes it a potential intelligent fluid 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Anionic surfactants have been utilized in foam-based underbalanced drilling. 16 These surfactants are well-regarded for their ability to produce stable and effective foams, which is a critical factor in improving drilling performance. Based on the literature review, commonly employed anionic surfactants include sodium dodecyl sulfate (SDS), 17 alpha olefin sulfonate (AOS), 18,19 and cetyltrimethylammonium Bromide (CTAB) 20 for drilling foams.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed that an elevated pressure resulted in smaller bubble radii and denser foam. Conversely, elevated temperatures tend to diminish foam stability due to surfactant degradation …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, elevated temperatures tend to diminish foam stability due to surfactant degradation. 11 The current literature presents a range of conflicting findings pertaining to the impact of salts on foam characterization. For instance, Guo et al 12 conducted an investigation into the influence of salt concentration on foam stability under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%